Influence of zinc additive and pH on the electrochemical activities of β-nickel hydroxide materials and its applications in secondary batteries. (February 2017) - Ravi kumar, C.R.; Kotteeswaran, P.; Raju, V. Bheema; Murugan, A.; Santosh, M.S.; Nagaswarupa, H.P.; Prashantha, S.C.; Kumar, M.R. Anil; Shivakumar, M.S.
Graphical abstract: Graphical representation of structural variation and interlayer distance of different Ni(OH)2 phases during charge-discharge and structure of Ni(OH)2 sample (inside). Highlights: β-Ni(OH)2 samples are synthesized using co-precipitation method. Electrochemical execution of β-Ni(OH)2 was examined utilizing CV and EIS studies. Reversibility of β-Ni(OH)2 electrode prolonged by zinc additive. Variation of pH was changing the charge transfer resistance and capacitance. Determine the capacitance of electrode by EIS study by using fitted circuit. Abstract: The importance of Ni-based batteries in the present context is extremely valuable, as their electrochemical properties are expected to offer significant insights into their application as battery materials. In this direction, Ni(OH)2 has been prepared using the co-precipitation method by varying the concentrations of zinc additive (2, 4, 6 & 8 wt%) and pH (8, 9, 10 & 11). The results show that the prepared samples exist in β-phase with flake like structure. The electrochemical properties of b-Ni(OH)2 have been investigated using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) measurements using a paste-type electrode on a nickel mesh as a current collector. The cyclic voltammetry measurements indicate that the reversibility of the electrode reaction increases at pH 10 and 6% Zn additive. Whereas, the EIS measurements reveal that a reduction in the charge transfer resistance increases the double layer capacitance of the nickel electrode.